The Effect Of Paylater Payment Methods On The Increase Of Impulse Purchases - Rinintha Parameswari; Puti Lenggo Ginny (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
This research was conducted based on the researcher's desire to find out what factors in the pay later payment method can foster impulse buying, especially for consumers. The independent factor being studied is the Paylater Method (X) while the dependent factor is impulse buying (Y), and the selection of the discount factor is due to the easy payment using the Paylater method. Based on the results of the questionnaire which was processed using SPSS 23 with simple linear regression, it was found that the factors studied had an influence of 4,023. And the result is that X has a positive effect on Y, while based on the results of the R2 count, the value = 0.294 or in other words the discount variable only answers 29.4% of the problems that occur.